2024
DOI: 10.1021/acs.chemmater.3c02408
|View full text |Cite
|
Sign up to set email alerts
|

Organic Cathodes, a Path toward Future Sustainable Batteries: Mirage or Realistic Future?

Jan Bitenc,
Klemen Pirnat,
Olivera Lužanin
et al.

Abstract: Organic active materials are seen as next-generation battery materials that could circumvent the sustainability and cost limitations connected with the current Li-ion battery technology while at the same time enabling novel battery functionalities like a bioderived feedstock, biodegradability, and mechanical flexibility. Many promising research results have recently been published. However, the reproducibility and comparison of the literature results are somehow limited due to highly variable electrode formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 153 publications
0
3
0
Order By: Relevance
“…Based on the electrochemical mechanism OEMs are classified as n -type, p -type, and bipolar type (having both n -type and p -type) . The n -type, p -type, and bipolar-type reactions are shown in Figure .…”
Section: Types Of Oemsmentioning
confidence: 99%
“…Based on the electrochemical mechanism OEMs are classified as n -type, p -type, and bipolar type (having both n -type and p -type) . The n -type, p -type, and bipolar-type reactions are shown in Figure .…”
Section: Types Of Oemsmentioning
confidence: 99%
“…Notably, organic materials usually composed of light elements (C, H, O, N, etc.) possess the various merits of eco-friendliness, structural tunability, and resource renewability, which have gained a lot of attention in the EES systems. Particularly, it was confirmed that the functional group of organic material is the key part for realizing the desired peculiarity . Moreover, according to the type of functionalities, the organic compounds could be defined as the various categories, such as sulfur compounds, amines, ethers, alcohols, and carbonyls. , Especially, among them, the carbonyl (CO) unit endowed with multiple properties has been actively explored. For example, the carbonyl moiety possesses a redox nature, which could be utilized for designing high theoretical capacity electrode materials via reversible electrochemical reactions .…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, organic electrode materials prove themselves as an alternative to replace the traditional cathode materials in terms of higher theoretical specific capacities, eco friendliness, high safety, and abundance in nature. [4][5][6] In this paper our aim is not to focus on cathode material but to discuss on the performance aspect of the herbal electrolyte. Electrolyte is one of the most critical and important internal components which is solution inside the batteries.…”
mentioning
confidence: 99%